Enhancing the immunogenicity of cancer vaccines by harnessing CLEC9A - M. H. Lahoud; K. J. Radford (Human Vaccines & Immunotherapeutics, 2022)
Dendritic cell (DC) vaccines are a safe and effective means of inducing tumor immune responses, however, a better understanding of DC biology is required in order to realize their full potential. Recent advances in DC biology have identified a crucial role for cDC1 in tumor immune responses, making this DC subset an attractive vaccine target. Human cDC1 exclusively express the C-type-lectin-like receptor, CLEC9A (DNGR-1) that plays an important role in cross-presentation, the process by which effective CD8+ T cell responses are generated. CLEC9A antibodies deliver antigen specifically to cDC1 for the induction of humoral, CD4+ and CD8+ T cell responses and are therefore promising candidates to develop as vaccines for infectious diseases and cancer. The development of human CLEC9A antibodies now facilitates their application as vaccines for cancer immunotherapy. Here we discuss the recent advances in CLEC9A targeting antibodies as vaccines for cancer and their translation to the clinic.